A Sensory-Diet database: A tool to characterise the sensory qualities of diets. (April 2016) - Lease, Haidee; Hendrie, Gilly A.; Poelman, Astrid A.M.; Delahunty, Conor; Cox, David N.
Highlights: Sensory characteristics of foods are known to partially drive food choice. Common foods (377) across the diet were described by 10 sensory characteristics. The tested foods were systematically assigned across the whole of a food/nutrient database. The sensory characteristics of whole diets can be assessed. Abstract: This paper describes the development of a Sensory-Diet database for understanding sensory drivers of food choice and how sensory characteristics influence food intake. Using an Australian children's national nutrition survey, foods were selected as representing the diet based upon frequency, food grouping, nutritional and/or sensory differences. Foods (377) were evaluated by a trained sensory panel for five basic tastes (sweet, sour, bitter, salt and umami), basic textures (hardness, cohesiveness of mass, moistness and fatty mouthfeel) and flavour intensity. A systematic methodology was developed to then assign the sensory values of the tested foods to all foods across the food composition database (3758 foods). Relationships between dietary sensory characteristics and composition were explored. Principal component analysis found diets were largely explained by a salty–sweet dimension in terms of flavour/taste and by cohesiveness, moistness and fatty mouthfeel in terms of texture. For foods evaluated by the trained sensory panel, significant correlations included those between sugar and sweetness; fat and fatty mouthfeel; sodium and salty and umami taste, and protein with salty taste. Across the diet, these correlations remained strong when applied to the entire food composition database with the exception of sodium and salty taste. In this case the relationship no longer held in more complex foods. The Sensory-Diet tool is the first published method for applying food sensory characteristics to a composition database to facilitate investigation of sensory characteristics, food composition and diet.